Deposition parameters and Raman crystal orientation measurements of ceria thin films deposited by spray pyrolysis. Issue 16 (22nd March 2022) - Simons, Philipp; Torres, Kierstin P.; Rupp, Jennifer L. M.
Abstract : Ceria thin films deposited by spray pyrolysis show a strong preferential 〈200〉 orientation after annealing corresponding to the 100 facet of high catalytic activity. This texture correlates with an unusually strong blue shift of the Raman F2g peak. Abstract : Spray pyrolysis offers excellent control over microstructure and cost-effective processing of ceria ceramic thin films for many applications such as catalysis, solid oxide fuel cells, solar-to-fuel conversion, and resistive switching. To control the properties of ceria thin films that are relevant for such applications, such as crystal orientation, grain size, crystallinity, and to achieve crack-free deposition, systematic processing guidelines for sprayed ceria are needed. In particular, the crystal orientation of ceria plays a significant role in the catalytic activity of ceria, and therefore controlling and measuring crystallite texture for catalytic applications is highly relevant for catalysis. In this work, we systematically scan the parameter space of deposition and post-annealing parameters to control various mechanical and structural properties that impact film functionality. We identify a critical film thickness of ceria during wet-chemical deposition of 300 nm in the initial amorphous phase, due to the interplay of ceria crystallization, solvent evaporation, and thermal expansion. Through XRD, the transition from amorphous to the cubic crystalline phases and grain growth with annealing is observed. Furthermore, a thermally induced, prominent shift in texture from the [111] to [200] direction is detected, which corresponds to the 100 ceria facet of high catalytic activity. Interestingly, we observe that the peak position of the Raman F2g stretching mode correlates with the measured texture coefficient and exceeds the bulk value of 465 cm −1 for highly textured films. While it has been previously observed that thermal annealing can induce stark texture in ceria thin films, we contribute with the new insight that Raman spectroscopy can be used to detect such texture. Overall, this offers a combination of cheap processing and simple characterization of the ceria crystal orientation.